Correction to “Redescription of Ololaelaps tasmanicus (Womersley, 1956) and description of a new species of Ololaelaps Berlese (Acari: Laelapidae) from Iran” - Babaeian, Esmaeil (Zootaxa, 2019)
There was an unfortunate error in a paper that appeared recently in Zootaxa (Babaeian et al., 2019). The addresses of two of the authors were listed incorrectly. The correct addresses of the authors are as follows: